2019
DOI: 10.5387/fms.2019-11
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence dimensions as predictors of coping reactions to stress in nursing practitioners

Abstract: Stress is an inevitable part of nursing life. Nurses need to respond to their stressful environment contents to reduce negative consequences. We examined the role of dimensions of emotional intelligence in predicting coping reactions to stress in 201 college nursing practitioners in this crosssectional study between November 2017 and January 2018. The nurses appraised their own emotions, but they were not sure that appraised others' emotions, regulated their and others' emotions. They could cope with new ideas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…One hundred and forty five studies investigated emotional intelligence ( n = 42,795) Nurses were investigated in 105 studies [ 20 , 79 , 80 , 82 , 91 , 102 , 213 , 216 , 227 314 ], 33 studies explored EI with medical doctors [ 239 , 253 , 257 , 265 , 315 – 342 ], three were in dentistry ( n = 661) [ 343 – 345 ], three studied EI in occupational therapists ( n = 1369) [ 346 348 ], two in physiotherapists ( n = 189) [ 349 , 350 ], one in radiologists ( n = 22) [ 351 ] and six collectively explored health professionals [ 31 , 342 , 352 355 ]. Meta-aggregation of 142 of the studies is provided in Table 4 ; the remaining three studies [ 227 , 236 , 351 ] were synthesised narratively.…”
Section: Resultsmentioning
confidence: 99%
“…One hundred and forty five studies investigated emotional intelligence ( n = 42,795) Nurses were investigated in 105 studies [ 20 , 79 , 80 , 82 , 91 , 102 , 213 , 216 , 227 314 ], 33 studies explored EI with medical doctors [ 239 , 253 , 257 , 265 , 315 – 342 ], three were in dentistry ( n = 661) [ 343 – 345 ], three studied EI in occupational therapists ( n = 1369) [ 346 348 ], two in physiotherapists ( n = 189) [ 349 , 350 ], one in radiologists ( n = 22) [ 351 ] and six collectively explored health professionals [ 31 , 342 , 352 355 ]. Meta-aggregation of 142 of the studies is provided in Table 4 ; the remaining three studies [ 227 , 236 , 351 ] were synthesised narratively.…”
Section: Resultsmentioning
confidence: 99%
“…It is particularly important to point to appropriate communication methods which would improve their functioning in the working environment, lower the impact of stress and effectively help manage it. It is also important to show the dependency between strong stress and an emotional state [52]. In this way, not only the necessary knowledge is delivered, but also a form of training is experienced.…”
Section: Discussionmentioning
confidence: 99%
“…› Emotional intelligence (EI) can be broadly defined as the ability to identify, express, evaluate, and instinctively self-regulate emotions; characteristics of EI include empathy, self-awareness, motivation, self-control, and adeptness in relationships (4,6,10,11,15) • The three primary models of EI differ in their definition, the discipline from which the model emerged, and the instrument used for measurement of EI (4,5,14) -The Trait Model (also called the Personality Model) was proposed by Reuven Bar-On, and originated in the field of community health. This model defines EI as a set of personality traits and noncognitive abilities that determine an individual's emotional and social adaptation (4,5,14) -Measurement tools based on the Trait Model include the Emotional Quotient Inventory and the Emotional Intelligence Questionnaire (4) -The Ability Model was introduced by John Mayer and Peter Salovey, and originated from results of cognitive research in the field of psychology.…”
Section: What We Knowmentioning
confidence: 99%
“…Accumulating evidence suggests that a similar correlation exists in the nursing workforce (3,4,5,6,7,8,9,10,11) • Investigators studying EI in nursing students and in nurses who are in clinical practice have reported (3,4,5,6) -positive correlations between the level of EI and delivery of bedside clinical care, clinical decision making, ethical behavior, parameters of physical and emotional wellness, more adaptive stress-coping strategies and effective conflict handling styles, longer career length, anticipated retention in current job, professional achievement, job satisfaction, adaptive responses to organizational change, levels of professionalism and self-compassion, self-reportsof clinical competence, patient perception of the level of nurse caring, and certain positive clinical outcomes in patients -In study of EI in 98 Dutch mental health nurses, researchers reported that mental health specialty nurses scored above average in EI as measured by the Emotional Quotient Inventory compared with nurses who were not working in a mental health specialty area (14) -Researchers in a study of 42 nurses using the Emotional Quotient Inventory found that successful staff nurses have average or high levels of EI (6) -Researchers have noted that high levels of EI are associated with strong onflict resolution skills in nurses, and that training regarding EI skills can promote effective conflict management in healthcare facilities (2) -Nurse researchers in Jordan noted significant positive associations between EI and self-reportedclinical performance among 194 nurses interviewed (1) -Although Baby Boomer nurses (i.e., nurses who were born during the period 1943-1960) may view Generation X nurses (i.e., nurses who were born during the period 1961-1980) and Generation Y nurses (i.e., nurses who were born during the period 1980-2000) as less caring, researchers in a study of 442 nurses found no significant differences in EI among nurses who represented the Baby Boomer generation, Generation X, and Generation Y. (3) (For more information on generational differences in nursing, see Evidence-Based Care Sheet: Nursing Workforce: Generational Differences ) -Researchers of a qualitative study on EI and effective management in nursing reported on the importance of implementing emotional and social learning programs to improve nurses' knowledge, skills, and attitudes essential to improvementing management in healthcare in order toachieve positive result, maintainpositive relations, and make accountable decisions (10) -negative associations between the level of EI and perceived level of stress and burnout (15) -In a cross-sectional stud...…”
Section: What We Knowmentioning
confidence: 99%
See 1 more Smart Citation